SAT0408 Long-Term Safety and Tolerability of Apremilast, an Oral Phosphodiesterase 4 Inhibitor, in Patients with Psoriatic Arthritis: Pooled Safety Analysis of Three Phase 3, Randomized, Controlled Trials. (10th June 2014) - Mease, P.J.; Kavanaugh, A.; Gladman, D.; Adebajo, A.O.; Gomez-Reino, J.J.; Wollenhaupt, J.; Cutolo, M.; Schett, G.; Lespessailles, E.; Shah, K.; Hu, C.; Stevens, R.; et al.
Abstract : Background: Apremilast (APR), an oral phosphodiesterase 4 inhibitor, works intracellularly to regulate inflammatory mediators. PALACE 1, 2, and 3 compared the efficacy and safety of APR with placebo (PBO) in patients with active PsA despite prior conventional DMARDs and/or biologics. Objectives: The overall safety and tolerability of APR was assessed in a pooled analysis of PALACE 1, 2, and 3, with APR exposure ≥52 wks. Methods: Patients were randomized 1:1:1 to PBO, APR 20 mg BID (APR20), or APR 30 mg BID (APR30) stratified by baseline (BL) DMARD use (yes/no). Patients with <20% reduction from BL in swollen or tender joint counts were required to be re-randomized to APR20 or APR30 if initially randomized to PBO, or continued on their initial APR dose. At Wk 24, all remaining PBO patients were re-randomized to APR20 or APR30. Patients taking concurrent DMARDs were allowed to continue stable doses (MTX, sulfasalazine, leflunomide, or a combination). Results: 1, 493 patients received study medication (PBO: 495; APR20: 501; APR30: 497) and were included in the safety population. The APR-exposure period included 720 patients treated with APR20 (766.4 patient-yrs) and 721 with APR30 (769.0 patient-yrs). The nature, incidence, and severity of AEs were comparable through the 24-wk and 52-wk periods (Table). The most common AEs were diarrhea (14.3%), nausea (12.6%), headache (10.1%), URTI (10.3%), and nasopharyngitis (7.4%). Most AEs were mild or moderate in severity. Discontinuations due to AEs (APR20: 7.5%; APR30: 8.3%) were low, occurring primarily in the first 24 wks of treatment. Serious AEs (SAEs) occurred in 6.8% (APR20) and 7.2% (APR30) of patients. One death occurred (APR20) due to multiorgan failure not suspected to be treatment-related. Diarrhea and nausea were predominantly mild and occurred at a reduced incidence after the first month of dosing, with the highest incidence reported in the first 2 wks of treatment. Most cases resolved within 30 days despite continued therapy and without medical intervention. Discontinuation due to GI AEs was 4% through Wk 52, with nausea (1.7%) and diarrhea (1.5%) being the most common. There was 1 case of diarrhea and 1 case of nausea reported as an SAE in the 0 to ≥24-wk period, and no additional cases reported in the 0 to ≥52-wk period. Exposure-adjusted incidence rates of major adverse cardiac events, serious infections including systemic opportunistic infection, or malignancies were comparable to PBO. Laboratory abnormalities were infrequent and transient with no trends or patterns observed. Conclusions: APR demonstrated an acceptable safety profile and was generally well tolerated through 52 wks; the nature, incidence, and severity of AEs were comparable through the 24-wk and 52-wk periods. These data do not indicate a need for laboratory monitoring. Disclosure of Interest: P. Mease Grant/research support: Celgene Corporation, Novartis, and Roche, Consultant for: Abbott, Amgen, Biogen Idec, Bristol-Myers Squibb, Genentech, Janssen, Eli Lilly, Pfizer Inc, and UCB, A. Kavanaugh Grant/research support: Abbott, Amgen, Astra-Zeneca, Bristol-Myers Squibb, Celgene Corporation, Centocor-Janssen, Pfizer Inc, Roche, and UCB, D. Gladman Grant/research support: AbbVie, Amgen, Bristol-Myers Squibb, Celgene Corporation, Janssen, Pfizer Inc, Novartis, and UCB, A. Adebajo: None declared, J. Gomez-Reino Grant/research support: Roche and Schering-Plough, Consultant for: Bristol-Myers Squibb, Pfizer Inc, Roche, Schering-Plough, and UCB SA, Speakers bureau: Bristol-Myers Squibb, Roche, Schering-Plough, and Wyeth, J. Wollenhaupt Grant/research support: Abbott, Bristol-Myers Squibb, MSD, Pfizer Inc, and UCB, M. Cutolo Grant/research support: Actelion, Bristol-Myers Squibb, and G. Schett Grant/research support: Abbott, Celgene Corporation, Roche, E. Lespessailles Grant/research support: Amgen, Eli Lilly, Novartis, and Servier, K. Shah Employee of: Celgene Corporation, C. Hu Employee of: Celgene Corporation, R. Stevens Employee of: Celgene Corporation, C. Edwards Grant/research support: Celgene Corporation, Pfizer Inc, Roche, and Samsung, Speakers bureau: Abbott, Glaxo-SmithKline, Pfizer Inc, and Roche, C. Birbara Grant/research support: Amgen, Bristol-Myers Squibb, Incyte, Eli Lilly, Merck, and DOI: 10.1136/annrheumdis-2014-eular.5589